Investigation of the essential oil from the peels of the fruit of Citrus reticulata Blanco var. szinkom - Condeno-Santelices, Cielo P. (Quezon City: College of Pharmacy, University of the Philippines, 1980.)
The fresh outer rind of the non-artifically colored mature fruit of Citrus reticulate Blanco var. szinkom was subjected to distillation using the Clevenger Apparatus for oils lighter than water. The volatile oil content was found to be 4.5%. The moisture content was found to be 69.8%.
The chemical and physical properties of the oil were also determined. Part of the oil was subjected to Thin Layer Chromatography. Ultraviolet Spectrophotometric Analaysis of said oil was also made ? including that of the isolates from the Preparative Thin Layer Chromatography. The UV Spectrophotometric Analyses were made using the Beckman Grating Spectrophotometer Model DB-G. IR Analysis using Beckman IR Spectrophotometer was also carried out.
The physical constants obtained were: optical rotation = levo 91.83; specific gravity, determined at 25°C = 0.8411 gram per mole; refractive index at 25°C = 1.4675; saponification value = 5.3; specific rotation = 109.2; and the aldehyde content calculated is 2.4%. the solubility of the oil using different solvents was also determined. The wavelength at maximum absorption is 216 nm
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, 1980.
Keywords: Mandarin orange; Essences and essential oils; Dalanghita